Do oval posts improve fracture resistance of teeth with oval root canals?. Issue 3 (1st September 2013) - Krastl, Gabriel; Lorch, Heiner; Zitzmann, Nicola U.; Addison, Owen; Dietrich, Thomas; Weiger, Roland
Abstract Aim To determine whether the use of oval posts increases fracture resistance of root canal treated teeth with oval‐shaped canals. Methods Extracted mandibular premolars with similar dimensions were decoronated. After root canal treatment, standardized post space preparations were performed to simulate the presence of oval‐shaped root canal morphologies. Specimens were randomly assigned to 3 groups (n = 3 × 24). In group SFP (small fiber post), circular posts with a cervical diameter of 1.5 mm were used without additional form‐congruent post space preparation. In group LFP (large fiber post), a circular post space preparation was performed to adapt posts with a cervical diameter of 1.9 mm. In group OFP (oval fiber post), oval posts with a long cervical diameter of 1.9 mm and short cervical diameter of 1.3 mm were utilized without additional post space preparation. Posts were cemented with dual‐cure resin. All specimens were restored with standardized direct composite crowns. After thermo‐mechanical loading in a computer‐controlled masticator, all specimens underwent fracture resistance testing. Means and standard deviations were calculated. Data were analyzed using the Kruskal–Wallis test (α = 0.05). Results The highest mean fracture load was observed in group OFP (273N ± 51), the lowest in group LFP (258N ± 72). Kruskal–Wallis indicated no significant differences in fracture resistance among the three experimental groups. Conclusions Within the limitations of this laboratory study, oval posts did not reveal increased fracture resistance of root canal‐treated premolars with oval‐shaped root canals compared with circular posts.